The newborn with congenital malformations - Mastroiacovo, Pierpaolo (Medicina e Morale, 2024)
Approximately 2% of all births have a malformation that requires some form of medical intervention. In about one third of cases, the malformation is so severe as to endanger the life of the newborn, and in fact congenital malformations account for 1/5 of the causes of death in the perinatal period